Model Pembelajaran Paired Storytelling Untuk Meningkatkan Keterampilan Menyimak Cerita Di Sekolah Dasar - Sri Mardiyanti; Ngatmini Ngatmini (Politeknik Kampar, 2023)
Listening activities are used more often than other language skills. However, students often have difficulty listening to learning. The pair storytelling model has been proven to improve learning processes and outcomes, one of which is students' listening skills. The purpose of this research is to find out how the pairing storytelling learning model can improve story listening skills in elementary schools. This research is expected to provide recommendations for teachers and educators in selecting and implementing effective learning models to develop students' listening skills. In addition, it can provide a better understanding of the importance of interactive and collaborative learning in improving students' listening skills. This research is a qualitativ research with a type of research approach in the form of literature studies or literature studies. The stages of the literature study method include; Identification of research objectives, Search for literature sources, Selection of Literary Sources, Analysis of Literary Sources, Synthesis and Interpretation. The results showed that Paired storytelling is an effective approach to improving listening skills and can overcome students listening difficulties and help improve their understanding of learning material.